2002
DOI: 10.1128/mcb.22.19.6906-6920.2002
|View full text |Cite
|
Sign up to set email alerts
|

Bni5p, a Septin-Interacting Protein, Is Required for Normal Septin Function and Cytokinesis in Saccharomyces cerevisiae

Abstract: In the budding yeast Saccharomyces cerevisiae, the Cdc3p, Cdc10p, Cdc11p, Cdc12p, and Sep7p/Shs1p septins assemble early in the cell cycle in a ring that marks the future cytokinetic site. The septins appear to be major structural components of a set of filaments at the mother-bud neck and function as a scaffold for recruiting proteins involved in cytokinesis and other processes. We isolated a novel gene, BNI5, as a dosage suppressor of the cdc12-6 growth defect. Overexpression of BNI5 also suppressed the grow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
99
0
2

Year Published

2002
2002
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(109 citation statements)
references
References 57 publications
7
99
0
2
Order By: Relevance
“…Further study of two cdc42 effector-loop mutants and of the roles of Bem3p, Rga1p, and Rga2p, which are three GTPase-activating proteins (GAPs) for Cdc42p (Zheng et al, 1993;Stevenson et al, 1995;Johnson, 1999;Smith et al, 2002), has suggested that Cdc42p GTPase cycling is involved in septin-ring formation (Gladfelter et al, 2002). In particular, it was suggested that Cdc42p, like the assembly GTPase EF-Tu in protein synthesis, participates in septin-ring formation by shuttling septin complexes to the assembling ring structure (Gladfelter et al, 2002), a view that contrasts with the more common view of activated (i.e., GTP-bound) Cdc42p activating effectors in signaling pathways in a Ras-like manner (Johnson, 1999).In addition to Cdc42p, its GEF, and its GAPs, several other proteins including Bni5p, Nap1p, and the protein kinases Cla4p, Gin4p, and Elm1p are also known to be involved in formation of the normal septin ring (Cvrcková et al, 1995;Longtine et al, 1998aLongtine et al, , 2000Sreenivasan and Kellogg, 1999;Bouquin et al, 2000;Weiss et al, 2000;Lee et al, 2002). Cla4p may function in the same pathway as Cdc42p, because it is a Cdc42p effector (Cvrcková et al, 1995;Weiss et al, 2000), although it is not clear whether the interaction between Cla4p and Cdc42p is required for its role in septin organization.…”
mentioning
confidence: 56%
See 2 more Smart Citations
“…Further study of two cdc42 effector-loop mutants and of the roles of Bem3p, Rga1p, and Rga2p, which are three GTPase-activating proteins (GAPs) for Cdc42p (Zheng et al, 1993;Stevenson et al, 1995;Johnson, 1999;Smith et al, 2002), has suggested that Cdc42p GTPase cycling is involved in septin-ring formation (Gladfelter et al, 2002). In particular, it was suggested that Cdc42p, like the assembly GTPase EF-Tu in protein synthesis, participates in septin-ring formation by shuttling septin complexes to the assembling ring structure (Gladfelter et al, 2002), a view that contrasts with the more common view of activated (i.e., GTP-bound) Cdc42p activating effectors in signaling pathways in a Ras-like manner (Johnson, 1999).In addition to Cdc42p, its GEF, and its GAPs, several other proteins including Bni5p, Nap1p, and the protein kinases Cla4p, Gin4p, and Elm1p are also known to be involved in formation of the normal septin ring (Cvrcková et al, 1995;Longtine et al, 1998aLongtine et al, , 2000Sreenivasan and Kellogg, 1999;Bouquin et al, 2000;Weiss et al, 2000;Lee et al, 2002). Cla4p may function in the same pathway as Cdc42p, because it is a Cdc42p effector (Cvrcková et al, 1995;Weiss et al, 2000), although it is not clear whether the interaction between Cla4p and Cdc42p is required for its role in septin organization.…”
mentioning
confidence: 56%
“…In addition to Cdc42p, its GEF, and its GAPs, several other proteins including Bni5p, Nap1p, and the protein kinases Cla4p, Gin4p, and Elm1p are also known to be involved in formation of the normal septin ring (Cvrcková et al, 1995;Longtine et al, 1998aLongtine et al, , 2000Sreenivasan and Kellogg, 1999;Bouquin et al, 2000;Weiss et al, 2000;Lee et al, 2002). Cla4p may function in the same pathway as Cdc42p, because it is a Cdc42p effector (Cvrcková et al, 1995;Weiss et al, 2000), although it is not clear whether the interaction between Cla4p and Cdc42p is required for its role in septin organization.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Those are proteins functioning in septin recruitment and ring assembly (see above), cytokinesis (see below), bud-site selection (Chant et al 1995;Sanders and Herskowitz 1996;Kang et al 2004), cell cycle control (Frenz et al 2000;Yoshida and Toh-e 2001), and mitotic signaling network (Carroll et al 1998;Longtine et al 1998Longtine et al , 2000Barral et al 1999;Lee et al 2002;. Septin serves as a scaffold for these proteins to localize and maintain at the bud neck.…”
mentioning
confidence: 99%
“…Approximately 15 min before bud emergence, septins are recruited to the presumptive bud site (Kim et al 1991), which depends on activated Rho-type GTPase Cdc42 and its effectors Gic1 and Gic2 (Iwase et al 2006). After recruitment at the incipient bud site, septins are reorganized and assembled as a higher-ordered ring structure at the mother-bud neck, which requires Cdc42, its GTPase-activating factors (Bem3, Rga1, and Rga2), Bni5, Nap1, Bni1, Cla4, Gin4, and Elm1 (Cvrckova et al 1995;Richman et al 1999;Bouquin et al 2000;Longtine et al 2000;Weiss et al 2000;Gladfelter et al 2001aGladfelter et al , 2002Gladfelter et al , 2004Lee et al 2002;Caviston et al 2003;Goehring et al 2003;Kadota et al 2004;Versele and Thorner 2004).…”
mentioning
confidence: 99%